Direct Current Stimulation Disrupts Endothelial Glycocalyx and Tight Junctions of the Blood-Brain Barrier in vitro - Xia, Yifan; Li, Yunfei; Khalid, Wasem; Bikson, Marom; Fu, Bingmei M. (Frontiers in Cell and Developmental Biology, 2021)
Transcranial direct current stimulation (tDCS) is a non-invasive physical therapy to treat many psychiatric disorders and to enhance memory and cognition in healthy individuals. Our recent studies showed that tDCS with the proper dosage and duration can transiently enhance the permeability (P) of the blood-brain barrier (BBB) in rat brain to various sized solutes. Based on the in vivo permeability data, a transport model for the paracellular pathway of the BBB also predicted that tDCS can transiently disrupt the endothelial glycocalyx (EG) and the tight junction between endothelial cells. To confirm these predictions and to investigate the structural mechanisms by which tDCS modulates P of the BBB, we directly quantified the EG and tight junctions of in vitro BBB models after DCS treatment. Human cerebral microvascular endothelial cells (hCMECs) and mouse brain microvascular endothelial cells (bEnd3) were cultured on the Transwell filter with 3 um pores to generate in vitro BBBs. After confluence, 0.1-1 mA/cm^2 DCS was applied for 5 and 10 min. TEER and P to dextran-70k of the in vitro BBB were measured, HS (heparan sulfate) and hyaluronic acid (HA) of EG was immuno-stained and quantified, as well as the tight junction ZO-1. We found disrupted EG and ZO-1 when P to dextran-70k was increased and TEER was decreased by the DCS. To further investigate the cellular signaling mechanism of DCS on the BBB permeability, we pretreated the in vitro BBB with a nitric oxide synthase (NOS) inhibitor, L-NMMA. L-NMMA diminished the effect of DCS on the BBB permeability by protecting the EG and reinforcing tight junctions. These in vitro results conform to the in vivo observations and confirm the model prediction that DCS can disrupt the EG and tight junction of the BBB. Nevertheless, the in vivo effects of DCS are transient which backup its safety in the clinical application. In conclusion, our current study directly elucidates the structural and signaling mechanisms by which DCS modulates the BBB permeability.